(untitled) (Development Service Industry Management, 2025)
Tax evasion is an urgent problem for any country, as this undermines the basics of the tax system and impedes the effective financing of government programs and services. Taxes are an integral part of the functioning of the state and providing public goods for citizens. They are the main source of budget revenues used to finance education, health care, infrastructure, defense and other important areas. However, despite its importance, tax evasion remains widespread in many countries around the world. Tax evasion can be defined as a deliberate concealment or reduction of tax liabilities, which is illegal and punishable in accordance with the law. The article analyzes the reasons for tax evasion (economic, institutional and legal, socio-psychological, technological and globalization) and economic consequences for Ukraine (failure to receive tax payments by the budget; suspension of the implementation of state programs; non-payment of salaries for budgetary. countries;Tax evasion directly leads to a significant loss of government revenues, limiting the possibility of financing public services and infrastructure projects, as well as a significant threat to phenomena and processes of economic and social nature and significantly destabilizes the development of the tax sphere, which requires the development of a complex of measures of effective counteraction. The measures to counteract tax evasion are outlined. The authors propose: improve the procedures for administration of taxes and compulsory payments, ensure their transparency; improving the institutional capacity of tax authorities, ensuring effective tax control, improving the quality of taxpayers’ service; creation of favorable conditions for conducting business and strengthening requirements for compliance with tax legislation.